Strategi Thariq bin Ziyad Menaklukkan Andalusia 711-714 M: Tariq bin Ziyad's Strategy to Conquer Andalusia 711-714 AD - Ritonga, Muhammad Akbar; Hamzah, Johan Septian Putera (Journal of Islamic History, 2021)
This research aims to interpret Thariq bin Ziyad’s policy with his miltary prowess in conquering Andalusia and describe socio-politic condition pre-war till end from konflik between Islam military and Christian Military di Andalusia. Hypotesis from this research is 1) Thariq bin Ziyad able to defeat their enemy in once attack without sharp strategy else. 2) the attack only for the coast district of Andalusia wtihout to invasion movement to middle land untill north of Andalusia. This research is library research with historical research method, they are: heuristic, verification, synthesis and historiography. Result of the research, prove that attack was succesfully carried out with a special strategy made by Thariq bin Ziyad in a period of almost a year of preparation as wel as defeating and killing the leader of the Visigoth Kingdom. As a result, Thariq and his military easliy conqeuring whole of Andalusia without war. Therefore, Thariq bin Ziyad’s policy or his intrique gave incridiblle effect for Islam Military, untill finally they able to occupy whole of Andalusia, although there is one district again had not chance to conquer it, because they are ordered by Caliphate of Umayyad to come back to Damascus.